BELANJA DAERAH DI BALIK DOMINASI DANA TRANSFER - Siti Nur Reskiyawati Said (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2025)
This study aims to analyze the development of Local Own-Source Revenue (PAD), Intergovernmental Transfers (Dana Perimbangan), and Regional Expenditure, as well as to identify indications of the Flypaper Effect in the Government of Maros Regency during the period 2021–2025. The study employed a quantitative descriptive approach using secondary data obtained from the Budget Realization Reports of Maros Regency. Data were collected through documentation and literature review methods. Data analysis was conducted using descriptive statistics and contribution analysis to examine the relationship between regional revenue sources and regional expenditure. The results indicate that Local Own-Source Revenue (PAD) increased during the study period; however, its contribution to Regional Expenditure remained relatively lower than that of Intergovernmental Transfers. Intergovernmental Transfers continued to be the largest source of revenue in the budget structure of Maros Regency and exerted a more dominant influence on Regional Expenditure. This condition suggests that Regional Expenditure is more responsive to transfer funds from the central government than to locally generated revenue. Therefore, the findings indicate the occurrence of the Flypaper Effect in the Government of Maros Regency during the study period. These findings imply that regional fiscal independence still needs to be strengthened through the optimization of local revenue sources in order to reduce dependence on central government transfers.